氷床コア中の溶存イオン成分の連続融解分析装置の開発 - 高, 田守昌; 平林, 幹啓; 東, 久美子; Remi, Dallmayr; 東, 信彦; Morimasa, Takata; Morihiro, Hirabayashi; Kumiko, Goto-Azuma; Nobuhiko, Azuma (2013)
Chemical constituents in ice core samples are proxy for past environmental condition of the earth. Conventional method for major ion analysis requies liquid samples preparation from ice core samples. Cutting and decontamination process of ice sample is labor work in cold laboratory and clean room. And these process make difficult for high spatial resolution analysis. Continuous Flow Analysis (CFA) system is developed by Sigg and others (1994) and it is applied for GRIP ice core analyis. This system foward the chamical analysis and improved resolution in mm order. Röthlsberger and others(2000) improved CFA for low concentration and firn sample. Present CFA system connects many analytical equipments in order to determinate many chamical species in liquid and composition of air. But uncertain of depth for each analysis is remained. We planed to develop CFA-IC system which is conbination of continuous melting of ice sample and chamical analysis using ion chromatography. Simillar system is already developed by Huber and others (2001) and therefore we made simillar flow line with this. Analysis speed ion chromatograpy is quite slow and unsuitable for CFA but it can analyse more than 10 ion species from same sample of 1cc and this is advantage for comparison with physical property analysis of ice core study. Present situation of our development is complete to make flow line and program of control/monitor for each devices. We are now making sequencial program for whole control of CFA system. 第4回極域科学シンポジウム 個別セッション：[OM] 気水圏 11月15日（金） 国立極地研究所 ３階ラウンジ conference object